Improved measurement of the Bd0 -B̄d0 oscillation frequency - BUSKULIC, D. (Institutional Knowledge at Singapore Management University, 1997)
The time dependence of B0 d {B 0 d oscillations is measured by the ALEPH experiment at LEP, using three techniques, two of which are updates of previous measurements. In all cases the charge of the decaying b quark and its decay time are measured in one hemisphere of the event; the quark charge at production is tagged mainly using the opposite hemisphere. The first method uses the charge correlation between a D and a lepton in the opposite hemisphere; if no lepton is present, the produced quark charge is determined from the hemisphere charges. In the second method, the decay time is measured using a lepton in one hemisphere and the initial state is inferred from the opposite-hemisphere jet charge. The third method uses a lepton in each hemisphere. The data used were collected from 1991 to 1994. The combined result is md = 0:436 0:033 ps1